2018
DOI: 10.1186/s13613-018-0394-6
|View full text |Cite
|
Sign up to set email alerts
|

The prognostic impact of abdominal surgery in cancer patients with neutropenic enterocolitis: a systematic review and meta-analysis, on behalf the Groupe de Recherche en Réanimation Respiratoire du patient d’Onco-Hématologie (GRRR-OH)

Abstract: Neutropenic enterocolitis (NE) is a diagnostic and therapeutic challenge associated with high mortality rates, with controversial opinions on its optimal management. Physicians are usually reluctant to select surgery as the first-choice treatment, concerns being raised regarding the potential risks associated with abdominal surgery during neutropenia. Nevertheless, no published studies comforted this idea, literature is scarce and surgery has never been compared to medical treatment. This review and meta-analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 65 publications
1
27
0
4
Order By: Relevance
“…Blood cultures and respiratory cultures should be obtained and sinus, head, chest, and abdominal imaging performed as indicated [14,15]. Abdominal pain or diarrhea associated with fever suggests neutropenic enterocolitis (typhlitis) which can lead to intestinal necrosis [28,29]. In the hemodynamically unstable patient with a central venous catheter, early catheter removal is associated with improved survival [19]; infected or potentially infected catheters should be removed without delay.…”
Section: Neutropenic Fever and Neutropenic Sepsismentioning
confidence: 99%
“…Blood cultures and respiratory cultures should be obtained and sinus, head, chest, and abdominal imaging performed as indicated [14,15]. Abdominal pain or diarrhea associated with fever suggests neutropenic enterocolitis (typhlitis) which can lead to intestinal necrosis [28,29]. In the hemodynamically unstable patient with a central venous catheter, early catheter removal is associated with improved survival [19]; infected or potentially infected catheters should be removed without delay.…”
Section: Neutropenic Fever and Neutropenic Sepsismentioning
confidence: 99%
“…In the absence of clinical benefit and in the presence of hemodynamic changes, the patient should be rapidly discussed with the surgeon for re-evaluation and possible surgery [21,37,38]. It has been reported that the presence of neutropenia should not be considered as a contraindication to surgery [39]. The mortality rate is high (32-50%), although it has been improving in recent years thanks to more efficient medical treatments [13].…”
Section: Introductionmentioning
confidence: 99%
“…Formerly referred to as typhlitis (from the Greek typhlon, or cecum), neutropenic enterocolitis (NEC) is a serious complication of neutropenia. It is characterized by segmental ulceration and intramural inflammation with necrosis of the gut (especially in the ileal-cecum-ascending colon area) [2,3]. NEC was first described in the 1970s as a complication of the treatment of childhood leukemias [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…It occurs most frequently after intensive chemotherapy in acute leukemias [7]. The actual incidence of NEC is unknown, and reports range from 0.8 to 26% [2,3,7]. NEC is considered as the most common gastrointestinal infection related to neutropenia [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation